How do you multiply #-y^3(2x^2y - 4xy^2)#?

1 Answer
Aug 4, 2015

Answer:

#=color(blue)(-2x^2y^4+ 4xy^5#

Explanation:

#−color(blue)(y^3)(2x^2y−4xy^2)#

Here, #color(blue)(y^3# needs to be multiplied with both terms within the bracket.

#=(−color(blue)(y^3))(2x^2y) −(−color(blue)(y^3))(4xy^2)#

#=-2x^2y*color(blue)(y^3) + 4xy^2*color(blue)(y^3#

  • As per property #color(blue)(a^m*a^n=a^(m+n)#

Applying the same to the exponents of #y#:

#=-2x^2y^color(blue)((3+1)) + 4xy^color(blue)((2+3))#

#=color(blue)(-2x^2y^4+ 4xy^5#